A Review On Concept Of Gulma In Ayurveda - Mohite, Priyadarshani Ashok; Jagtap, Umesh Balaso; Shah, Sonal (International Research Journal of Ayurveda & Yoga, 2021)
Introduction Gulma is a disease entity linked to Vata (a bodily humour) that encompasses a wide range of gastrointestinal and gynaecological disorders, however because to its complex clinical presentation, diagnosis can be challenging. As a result, a thorough understanding of Gulma is required for precise and straightforward diagnosis. Aims and objectives To conduct a Nidanatmaka (Epidemiological) study of Gulma in context of Dosha predominance. Material and methods Classical Ayurvedic books, particularly the Charaka Samhita, were thoroughly examined, together with Sanskrit commentary, to compile a list of relevant references. A thorough search of the Internet was conducted to locate prior study papers and related material. Results Shotha (Inflammation) and Shula have a close bond with Gulma (Pain). The main causal variables are deranged Agni (Digestion & Metabolism vv) and emaciated Dhatu (Tissues), which provoke Vata by raising its Ruksha Guna (Dryness) or inhibiting its functioning (Avarana) Conclusion Gulma is primarily Vata Dosha provoking. It can be found on the surface or deep within the Thoraco abdominal cavity, and it might be palpable or not. Shotha is the basic phenomenon that causes Gulma’s pathogenesis, and Shula is the Cardinal Symptom. In comparison to Prakriti Sama Samaveta , where the result is perfectly in accordance with the cause, Vikriti Vishama Samaveta varieties of Dwandwaja Gulma require specific treatment.